Pengaruh Likuiditas, Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Manajemen Pajak Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Pramanaswari, AA Sagung Istri; Desak Ayu Sriary Bhegawati; I Kadek Bagiana (Universitas Katolik Widya Karya Malang, 2025)
The point of this study is to find out how liquidity, revenue, debt, and the size of the company affect tax management. Liquidity, revenue, debt, and company size are some of the independent factors. Tax management is the dependent variable. This study examined manufacturing companies listed on the Indonesia Stock Exchange that are part of the Consumer Goods Industry Sector and the Pharmaceutical Subsector. Companies that make medicine market goods are important to modern problems in tax management. Purposive sampling was used by the researcher to choose the group that was used to analyze the study. For this type of study, numerical data is used, specifically the financial records of industrial companies traded on the Indonesia Stock Exchange from 2019 to 2023. The researchers got the data they used from the Indonesia Stock Exchange (IDX) through www.idx.co.id, which is the main website of the Indonesia Stock Exchange. A linear regression test was used to look at the data and to test the theory of this study. There is a traditional assumption test that is done before the regression is used. The study's findings show that cash and leverage have good impact for income tax management. Meanwhile, making money and the size of the business harm tax management.